Pemetaan Persebaran Penyakit Malaria di Kecamatan Punduh Pidada, Kabupaten Pesawaran, Provinsi Lampung - Nugraheni, Irma Lusi; Usman, Mustofa; Sutarto, Sutarto (Jurnal Spatial Wahana Komunikasi dan Informasi Geografi, 2023)
Malaria transmission in Pesawaran District has decreased for three consecutive years, namely 2018-2020 where it reached an API rate of 0.67 per 1000 population. In 2020 Punduh Pidada District has 28 positive cases of malaria. Factors that influence the number of cases of malaria transmission include environmental factors such as rainfall, land use, and altitude. The purpose of this study was to determine the distribution of malaria in terms of transmission factors in the form of environmental factors in the form of land use and topography. The method used in this research is qualitative with descriptive analysis. Data analysis techniques in this study are buffering techniques and map analysis. The results of this study indicate that land use and topography have an influence on the number of cases of malaria transmission in Punduh Pidada District. The land uses that had the highest cases were mixed forest (18 cases), plantations (18 cases), settlements (20 cases), and fish ponds (20 cases). Meanwhile, the altitude/topography of less than 200 meters above sea level covers all sample locations of malaria transmission in Punduh Pidada District in 2016-2021.